(untitled) (Research, Society and Development, 2021)
This study aims to identify factors associated with Traffic Accidents (TA) among university students and verify the association between risky behavior and TA in this population. This is a cross-sectional, exploratory study with undergraduate students from a public university in Bahia, in 2019. 276 students participated, mostly women (74.6%). Of the university students, 55 were involved in TA, the highest prevalence was for females (63.6%), single (17.8%), those whose father did not complete primary school (47.2%), who did not work (49%), and motorcycle drivers (49%), showing an association with the outcome, p = 0.036, p = <0.001, p = 0.014, p = 0.001, p = <0.001, respectively. Working in addition to studying, being a user of the motorcycle driver category, and driving a motorcycle, a greater chance of having a relationship with AT, 1.54, 1.28, 1.95 times, respectively. Whereas students who studied parents / family members who always respected the traffic rules dissipated 45% less chance of having spread in TA.